HPLC, GC-MS, XRD profiling, enzyme inhibition and cytotoxicity potential of Phlomis Stewartii extracts using response surface methodology - Mamoon Ur Rasheed; Haroon Rashid; Shifa Iman; Sadaf Oranab; Muhammad Abdul Rahim; Mohamed H. Mahmoud; Roberto Castro-Muñoz; Eliasse Zongo (BMC Plant Biology)
Abstract The mechanical extraction of various phytochemicals from Phlomis stewartii (P. stewartii) was modeled using response surface methodology (RSM). The Box-Behnken design (BBD) was used to optimize the three independent variables comprising of 17 experimental runs, with the experiments randomly arranged to minimize the effects of unexpected variation in the observed dependent variables {extraction yield, total phenolic content (TPC), and total flavonoid content (TFC)} due to systematic errors. The speed (X1, 100, 150 and 200 rpm), solvent volume (X2, 100 and 150 and 200 mL), and extraction time (X3, 2, 5 and 100 h) at 3-levels (high and low coded levels) were used to evaluate BBD of RSM. Results showed that the maximum value of yield, TPC and TFC in leaves ethanol extracts (LEE); flower ethanol extract (FEE), and whole plant ethanol extracts (WPEE) were observed at the following extraction conditions: A X1 of 150 rpm, X2 of 200 mL and X3 at 8 h. The minimum values were observed at an X1 of 150 rpm, X2 of 100 mL and X3 of 2 h. Analysis of variance (ANOVA) and the interaction effects of independent factors showed that X2 and X3 significantly positively influenced the response variables. These values closely matched the predicted yield, TPC and TFC. High-performance liquid chromatography (HPLC) analysis reveals that hydroxybenzoic acid, p-coumaric acid, gallic acid, chlorogenic acid, and salicylic acid, are the major secondary metabolites in the extracts. Gas chromatography-mass spectrometry (GC-MS) analysis showed the presence of different compounds such as thiazole, 2-ethylacridine, silicic acid, arsenous acid, 3,5-ethanoquinolin-10-one, and hexahydropyridine. All these identified compounds exhibit a wide range of various biological potential, including anti-viral, anti-inflammatory, anti-diabetic and anti-bacterial activities. The highest α-amylase inhibitory potential IC50 (53.33 ± 0.21 µg/mL), and α-glucosidase inhibitory potential IC50 (51.07 ± 0.17 µg/mL) were shown by LEE extracts. The study concludes that LEE extracts may have anti-inflammatory, immunomodulatory, antioxidant, hepatoprotective, and nephroprotective potential, suggesting potential for further investigation in diabetes management. Graphical Abstract